Changing landscape of first-line treatment for locally advanced or metastatic urothelial carcinoma: the progression from platinum-based chemotherapy to platinum-free therapy - Liu, Zengguang; Chen, Chen; Yin, Jiaxin; Cong, Xiaofeng; Liu, Ziling (Frontiers in Immunology, 2025)
Urothelial carcinoma (UC) represents the most common pathological type of bladder cancer. For patients with locally advanced or metastatic UC (la/m UC), the standard of care with platinum-based chemotherapy as the cornerstone has greatly improved the survival time. Although the platinum-containing regimens have been established as the first-line therapeutic approach for la/m UC and demonstrate high initial response rates, most patients experience disease recurrence or metastasis shortly after treatment cessation, compounded by the inherent toxicity associated with platinum agents, which collectively pose substantial challenges to long-term patient survival. Moreover, some patients are ineligible to receive a platinum containing therapy, which greatly affects their potential possible benefit. With the success of the EV-302 study, the combination of enfortumab-vedotin (EV) and pembrolizumab has supplanted chemotherapy as the current standard of care for the first-line treatment of la/m UC, thus initiating a treatment paradigm of platinum-free for the first-line treatment of la/m UC. In recent years, the treatment landscape of la/m UC has witnessed remarkable shifts, evolving from traditional chemotherapy to the emerging “chemotherapy-free (platinum-free)” strategy. This article provides a comprehensive review of the historical development and outlook of first-line treatment strategies for la/m UC, including the role of chemotherapy, the rise of platinum-free and its clinical applications. Through this in - depth exploration, the article endeavors to offer readers a holistic understanding of the present treatment panorama for la/m UC, furnishing them with profound insights into the transformative trajectory and emerging trends within la/m UC treatment strategies.